PENGGUNAAN ALAT PERAGA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD INPRES TASIU II, KALULU, MAMUJU PADA MATERI IPA - Arief, Siti Ni’mah; Sa’adah, Hurin Innihayatus; Sumadi, Sumadi (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2024)
The role of the teacher in delivering learning materials is very influential on student understanding. Teachers lack mastery of learning techniques, teachers are less competent in using learning media, cannot choose models that are in accordance with the learning theme, and the methods used are still lecture methods, often making students bored and passive when in class, so that it can reduce students' enthusiasm for learning. The purpose of this study was to determine the learning outcomes of fifth grade students by using science material props on the theme "Heat and Its Transfer". This research method uses Classroom Action Research (PTK) with a qualitative approach. The research subjects amounted to 16 students. The research was conducted for one month. Written test instruments were used for data collection. Test sheets, worksheets, and observation sheets were checked during data processing. Based on the results of the Classroom Action Research, the average value of each cycle I and II in subtheme 1 "Temperature and Heat" and theme 6 "Heat and Its Transfer" has increased to 73.12 and 83.18 respectively. Thus it can be concluded that classroom action research (PTK) SD Inpres Tasiu II with props can improve student learning outcomes.